2013
DOI: 10.1177/0218492313504420
|View full text |Cite
|
Sign up to set email alerts
|

Differential release kinetics of cardiac biomarkers in off-pump coronary bypass

Abstract: Even in patients undergoing off-pump surgery, there is significant natriuretic peptide and myocardial enzyme release. Only B-type natriuretic peptide levels had an association with postoperative variables.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…The results of the second study showed that valvular pathologies, such as AS and MR, were associated with higher preoperative NT-proBNP levels than CAD, upon admission to surgery. This finding was consistent with previous studies [106][107][108][109][110][111][112][113] . The novelty of this finding was that it held true, even after adjusting for known confounders.…”
Section: Nt-probnp and Phfsupporting
confidence: 94%
“…The results of the second study showed that valvular pathologies, such as AS and MR, were associated with higher preoperative NT-proBNP levels than CAD, upon admission to surgery. This finding was consistent with previous studies [106][107][108][109][110][111][112][113] . The novelty of this finding was that it held true, even after adjusting for known confounders.…”
Section: Nt-probnp and Phfsupporting
confidence: 94%
“…High plasma concentrations of NT-proBNP and BNP postoperatively were associated with increased use of inotropic drugs and/or intra-aortic balloon pump 2,55,71,[73][74][75][76] . High levels of natriuretic peptides were also reported to be associated with adverse short-term outcome, such as prolonged ICU stay, ventilation time, in-hospital mortality and postoperative mortality 72,73,77,78 .…”
Section: Postoperative Bnp and Nt-probnp In Cardiac Surgerymentioning
confidence: 99%